(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
According to author the common people are shown in open revolt againstall types of exploitation and deprivation. This sort of uprising on their partnaturally turns out to be revolt against kings and lords. In the process, theiractive participation becomes a positive change in the social and the politicalcomposition of the times. They even endeavor to capture power. In any case,their active efforts in this direction shake the very foundation of the feudalsociety and pose a serious threat to the political supremacy of elite and inconsequence herald the dawn of new age.